Gaya Hidup dan Perilaku Konsumtif Remaja di Manado - Muhammad Kamil Jafar; Nur Evira Anggrainy; Irgiyani Suhardin; Rahmawati Nadila Tohai (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2023)
This article aims to describe the consumerist behavior of teenagers in the city of Manado. This research uses a qualitative research method with a descriptive approach, the informants in this research are teenagers who have been determined deliberately, the data collection technique is carried out in two ways, namely observation and interviews, the analysis used is in three stages, namely data collection, data sorting, and drawing conclusions. . The research results show that teenagers' behavior becomes consumptive because they buy goods that do not suit their needs and follow the lifestyle of the adults around them. So they produce behavior that is no longer based on rational considerations.